Trigliserid yağların yeni bir yöntemle stirenlenmesi - Güner, F. Seniha (Fen Bilimleri Enstitüsü, 1993)
St irenin kuruyan yağlarla kopol imer i zasy onundan kuruma süreleri kısa. suya ve kimyasal maddelere karşı dayanıklı ve sert filmler oluşturan ürünler elde edilir. Klasik yöntemler ile yağların stirenlenmesinde yağla rın yapısındaki yag asitlerinin içerdikleri çift bağların sayısı ve pozisyonu önemlidir. Geliştirdiğimiz üretim yönteminde ise reaksiyonun gerçekleşmesinde yag asitlerin- deki çift bağların etkisi yoktur. Böylece kuruyan yağla rın yanı sıra yarı kuruyan yağlar da stirenlenebilmekte- dir. Geliştirilen yeni yöntemde, yağın yapısına, ısı etki si ile kolayca parçalanıp serbest radikal oluşturabilen azo grubu sokulmuş, daha sonra 70"C'da stiren ile kopol i- merizasyon reaksiyonu gerçekleştirilmiştir. Çalışmada yag komponenti olarak ayçiçeği yağı, tütün yağı, haşhaş yağı ve keten yağı kullanılmıştır. Elde edilen stirenlenmiş ürünlerin film özelliklerinin incelenmesi ile yüzey kapla- yıcı olarak kullanılabilecekleri sonucuna varılmıştır.

Styrenation of drying oils and alkyds is a well known process which finds practical application in organic coatings. The term styrenation refers to copolymerization of styrene (St) with oils or alkyds induced in the presence or absence of an added initiator such as benzoyl peroxide. The mode of styrenation depends on the type of oil used. The presence of conjugation in the oil favors copolymerization which can be activated thermally even without initiator. In the case of non-conjugated oils, however, copolymerization can be motivated by adding peroxides, pre-blowing the oil, and Lewis acid catalysts such as BF3. Semi-drying and non-conjugated drying oils may be mixed with conjugated oils to yield better styrenated products. Typical reactions, postulated for the styrenation of non-conjugated drying oils in the presence of benzoyl peroxide, are depicted below. O 0 ı-C-0-O-C-Ph »» 2 Ph-C-O- Ph-C-0-O-C-Ph »» 2 Ph-C-O- (1) O Ph-C-O* » Ph- + C0a (2) CH CH CH !h Ph- + CHa - »> Ph-H + CH» (3) CH CH CH CH I I VI h CH' + n CHa=CH ^ Copolymer (4) CH Ph İH I Ph* + CHa=CH ^ Homopolystyrene (5) k Notably, homopolymerization of St can be initiated by the primary radicals, produced from the thermolysis of benzoyl peroxide, as indicated by reaction 5. Consequently, the resulting product is a mixture of copolymer and homopolymer. The practical application of St of non-conjugated oils by peroxides is» therefore, strongly hampered by the formation of homo-polystyrene, since polystyrene is not compatible with the oils, the mixture separates and the product is turbid and unsatisfactory. In the present work, the styrenation of several semi- drying oils, namely tobacco seed oil, poppy seed oil and sunflower oil and a drying oil, linseed oil, has been achieved by the use of a low molecular weigth azo initiator, (4,4'-azobis(4-cyanopentanoic acid) (ACPA) ) incorporated to the partial glycerides. Attachment of azo groups to the oils was achieved by condensation of ACPC with the partial glycerides according to the following reaction. VII O CH3 CH3 O - OH + Cl-C-CHa-CH2-C-N=N-C-CHa-CHa-C-Cl + CN CN HO l pyridine (6) h O CH3 CH3 O - 0-C-CHa-CHa-C-N=N-C-CHa-CH2-C-0- | CN CN Partial glyceride backbone Styrenation of the oils was achieved by the thermolysis of the lateral azo group attached to the glycerolysate. The overall reaction may be generalized as fol lows. h 0 CH3 CH3 O 0-C-CHa-CHa-C-N=N-C-CHa-CH3-C-0 CN CN 1 (?) h O CH3 O-C-CHa-CHa-C. İN I" (8) VIII h O CH3 )-C-CHa-CH2-C CN Partial glyceride segment Polystyrene segment In these experiments, overall conversion of St was in the range of 60-75 %. Typical results concerning viscosities of each styrenated oil based on partial glycerides with two initial hydroxy 1 values, are represented in Table 1. As can be seen, viscosities are significantly lower when the partial glycerides with lower hydroxyl values are utilised. As it was previously noted lower hydroxyl value corresponds to higher proportion of unfunctionalised glyceride molecules, as far as azo groups are concerned, which do not actively participate in the styrenation process and greatly reduce the viscosity of the final product. The applied tests for determining the film properties and the obtained results are given in Table 2. As stated in Table 2 gelation was observed after adding driers in the case of styrenated linseed oil glycerolysate of higher hydroxyl value. This indicates the importance of the type of oil used in the process. Although final film properties vary according to the type of oil used, it is quite clear that the oils styrenated via this procedure show much better alkali resistance and dry fast as the styrenated linseed oil samples obtained by classical methods. We have also performed styrenation experiments using allyl malonate as a degradative chain transfer agent. It is well known that termination of St polymerization occurs almost exclusively by a combination process for temperatu res up to 80 'C. This reaction leads crossl inking and eventual inhomogeneity in the styrenated product. One way to overcome crosl inking is the use of classical chain transfer agents during the styrenation process. However, because of the fact that propagating active radicals are transferred to the chain transfer agent, homopolystyrene formation is unavoidable and undesirable. IX 01 -p o 3.d o u a, ?d © ?p (O C © >,.P en © 42 4-> -P.M 01 o o 01 r-l © 43 E- -p c © -p c o o o 01 o.o o -p © c © 45 -P ?d © c c.H 45 -P © İM I 01 © ı-H CO © 4J 10 C O ı- I S O © o e (D oı A © ?P -o 03 İH (0 o. © İH Cm m ?d ©.p ıa c 0) İH >N.P cn d) X. -P oı (D ?rl -P İH © a o İH a, 6 r-H ?H En © r-4 « © rC ?P c o M O (0 İH u o c c o.rl ?P 3 rH O 01 § 10 ©aç oı CN "d © +J -rl «O rH c o.r! -P 3 rH O 01 o* X ut 3 «3 ü rC ü in cn -d c.rl O U +J 3 O -d ©.rl u u 01 © İH © -d a c a-ri a) oı rQ o rC -M © a -p 01 © +J I1 3 SO u ?d 4H d) O -rl rH İH 10 o m CN -p ? + RS« (9) H RS- + CH2=CH m- RS/^v^^^CH2-CH (10) Ph Ph R-SH : A mercaptan type chain transfer agent. In our styrenation experiments, the polymerization of St is regarded to proceed entirely with the unimolecular termination mechanism as shown below. For this reason allyl compounds may be termed more correctly as degenerative chain transfer agents. + CH2=CH-CH2-CH ( COOEt )2 ^ (11) + CH2=CH-CH-CH ( COOEt ) 2 H Because allyl compounds lead to degradative chain trasfer, the resulting allyl radical is quite stable due to the allyl resonance. CH2=CH-CH-CH ( COOEt ) 2 ^ - CH-CH=CH-CH ( COOEt ) 2 (12) In this case conversions were in the range of 45-60 %. Table 3 lists the film properties of the resultant products obtained in the presence of allyl malonate. It should also be noted that the use of allyl malonate improves the film flexibility and adhesion. This behaivor is expected since allyl compound regulates the chain length of St segment, e.g., short polystyrene chains are formed. This is also confirmed by the viscosity values of styrenated oils. Comparison of the viscosity data on the styrenated products in the presence and absence of allyl malonate (Table 1), shows that the XII © +J 10 c o ı-H S *P O © c -d d) d) tn -d a, o c © Tİ 43 -P © İH C (0 ?rt 03 ?d © O) f-H İh Q. <0 S a « © CQ PL, >-ı.ri m o ı-H.n -d O © © ?d to © c +J -ri (O ?-* c © "d u © 4J 0 Cfî c © 0 >, -p 01 03 ©.ı-l ı-H -P ıö u c © o O -P c © > c o ?rl O rt ~ cn © 43 «S -p © >. ri -P (0 i-H © !h â? o VO ?d d 10 B ı-H.ri l(H © 42 P d o X o (0 İH o o d d o.ri.P ı-H O 03 X O o © d? 03 d o.rt.p 3 r-H O 01 o* CO 3 10 O 4= ü m cti ?d d u -n o cj m. CM "d ©.P -rt JC).- ı a a 10 oı m o 43 -P rt 4J -H 3 >xO ü ?d m a) O -rt -p +j 03 03 © © o cn S3 -p 01 © m CM.p (0.p 3 O ?d © ?ri U IÖ ü 03 I.p 03 © ı0 43 ü -d © 03 ©.P 3 d.rt S 8 !h 3 O 43 © Öl d 10 43 O O d o d m.d d © bı ©,-1 XIII viscosity of the product in the presence of allyl malonate is 1 ower. These results show that a new initiation system based on the thermolysis of the azo groups incorporated to partial glycerides is found to be useful in styrenation of triglyceride oils. The advantages of using this system are manyfold, mainly, (1) it does not require additional initiator or catalyst (2) absence of homopolystyrene formation due to the direct generation of active radical sites on the oil backbone (3) cross linking reactions observed generally in styrenation process may be prevented by the addition of degradative chain transfer agent (4) more importantly, this process allows styrenation of semi- drying oils without mixing with oils having conjugated double bonds or using blown oils.
A New method for the styrenation of triglyceride oils for surface coatings
Tez (Doktora)-- İTÜ Fen Bil. Enst., 1993.
Keywords: Kopolimerleşme; Stiren; Yağlar; Copolymerization; Styrene; Oils